International business cycle synchronization: A synthetic assessment - Hyun-Hoon Lee; Cyn-Young Park; Ju Hyun Pyun (Asian Development Bank (ADB), 2022)
We synthetically assess the three major transmission channels of international business cycles: bilateral trade, foreign direct investment (FDI), and portfolio investment flows between economies with multiple fixed effects. Using the data of 72 economies during 2010-2019, we find that real and financial integration generates heterogeneous impacts on business cycle comovement. Trade integration, particularly through intermediate input trade, drives business cycle synchronization. We also find greenfield FDI leads business cycle comovements. This may be due to deepening intra-industry trade and dense global value chains. Higher debt market integration is also associated with more synchronized business cycle comovement, implying that balance sheet effects and the related credit cycle can exert influence on business cycle comovements. However, equity integration leads to business cycle divergence, suggesting that cross-border equity holdings may help stabilize transmission of a foreign economy's shocks.
Keywords: F15; F21; F34; F44; 330; business cycle synchronization; trade; FDI; portfolio investment